2019
DOI: 10.1186/s13027-019-0262-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evolutionarily novel genes are expressed in transgenic fish tumors and their orthologs are involved in development of progressive traits in humans

Abstract: Earlier we suggested a new hypothesis of the possible evolutionary role of hereditary tumors (Kozlov, Evolution by tumor Neofunctionalization, 2014), and described a new class of genes – tumor specifically expressed, evolutionarily novel (TSEEN) genes - that are predicted by this hypothesis (Kozlov, Infect Agents Cancer 11:34, 2016). In this paper we studied evolutionarily novel genes expressed in fish tumors after regression, as a model of evolving organs. As evolutionarily novel genes may not yet have organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Furthermore, it was noted that the expression of some evolutionarily young genes occurs specifically or preferentially in tumors. These genes were termed tumor-specifically expressed, evolutionarily novel (TSEEN) [ 38 , 98 ]. Moreover, it has been reported that new genes are also overrepresented among the testis and brain.…”
Section: Phylogeny Of Cancer-related Retrogenesmentioning
confidence: 99%
“…Furthermore, it was noted that the expression of some evolutionarily young genes occurs specifically or preferentially in tumors. These genes were termed tumor-specifically expressed, evolutionarily novel (TSEEN) [ 38 , 98 ]. Moreover, it has been reported that new genes are also overrepresented among the testis and brain.…”
Section: Phylogeny Of Cancer-related Retrogenesmentioning
confidence: 99%
“…Several non-trivial predictions of the main hypothesis have been confirmed in my laboratory ([ 1 4 ], reviewed in [ 5 ]). One non-trivial prediction of the main hypothesis is that evolutionarily novel organs if they indeed originated from hereditary tumors or tumor-like structures, should recapitulate some features of tumors in their development.…”
Section: Introductionmentioning
confidence: 83%
“…The prediction about the expression of evolutionarily novel genes in tumors was confirmed in many publications from our lab. As a result, a new class of genes—tumor specifically expressed, evolutionarily novel (TSEEN) genes—have been described (reviewed in [ 19 ]; see also [ 12 , 20 ]). The predicted parallel evolution of oncogenes, tumor suppressor genes, and differentiation genes was confirmed using in silico genomic analysis [ 12 ].…”
Section: Background: the Theory Of Carcino-evo-devomentioning
confidence: 99%
“…In the same paper, the predicted correspondence of the number of oncogenes to the number of differentiated cell types was verified [ 12 ]. The acquisition of progressive functions, not encountered in fishes, by human orthologs of fish TSEEN genes, was proven using a transgenic zebrafish inducible tumor model [ 20 ]. This paper is considered by many specialists as the direct confirmation of the main hypothesis.…”
Section: Background: the Theory Of Carcino-evo-devomentioning
confidence: 99%
See 1 more Smart Citation